Selectivity and efficiency of herbicide mixtures on weed control - Azevedo, Demóstenes Marcos P. de; Nóbrega, Laudemiro Baldoíno da; Beltrão, Napoleão Esberard de M. (Pesquisa Agropecuaria Brasileira, 2014)
In order to study the efficacity of several herbicide mixtures against weeds and their phitotoxicity effects on cotton (Gossypium hirsutum var. latifolium L.) a field trial was placed at Experimental Station of Surubim, PE, Brazil, in 1980. The results showed that: 1. the mixtures, indistinctly, showed to be selective to cotton plant and effective on controlling weeds by a period of approximately 60 days; 2. the modality of applying alachlor + diuron and pendimenthalin + diuron (pre-emergent or pre-sowing incorporated) did not affect their selectivity, efficiency on controlling weeds, cotton seed productivity, and fiber quality either; 3. the tested mixtures did not influence phenological cotton plant characteristics, component production, seed cotton field and technological fiber qualities; and 4. the highest cotton production was obtained by the treatments metolachlor + diuron, and alachlor+ diuron, without, however, differing statistically from the other herbicide mixtures.